Prevalence and impact of Helicobacter pylori in dyspepsia - Srinivas, Y.; Prasad, P. Kameshwari; Sai, N. Divya (International Surgery Journal, 2016)
Background: Functional dyspepsia is considered to possess a wide spectrum of non specific upper gastrointestinal symptoms without any organic alteration, accounting for 60% of patient referrals to gastroenterology clinics. The objective was to study the prevalence of Helicobacter pylori in patients with dyspepsia undergoing upper G. I. endoscopy. Methods: 100 cases of dyspepsia, studied clinically as per the proforma over a period of one and half years from October 2010 to November 2012, were subjected to upper gastro-intestinal endoscopy under topical anesthesia, during which biopsies, from the antrum was taken. Biopsy specimens were immediately placed onto a unit containing urea and an indicator. Positive test (rapid urease test) for Helicobacter pylori was indicated by change in color of the medium from yellow to pink or red. The case was taken as Helicobacter pylori positive when the rapid urease test was positive. Results: Out of 100 patients, with mean age of 41.8 years, 36 patients were diagnosed to have been infected with Helicobacter pylori (36%). Conclusions: In this study, we found that Helicobacter pylori were consistently associated with peptic ulcer disease, which is in broad agreement with the studies done earlier. Thus we conclude that, Helicobacter pylori infection may have a role in the etiopathogenesis of peptic ulcer disease.